The Role of Madrasah Committee in Improving The Quality of Islamic Education at MTs Negeri 2 Pasaman in 2018-2020 - Yurnalis Yurnalis; Ahmad Lahmi; Rahmi Rahmi (Universitas Muhammadiyah Pontianak, 2022)
The quality of education in every educational institution cannot be separated from the committee, therefore, this study aims to describe the role of the committee at MTs Negeri 2 Pasaman in improving the quality of Islamic education. This study was carried out with a qualitative approach through ex-post-facto because the data analyzed were events in the past, namely in 2018-2020. Based on the results, the madrasa committee has a role in providing ideas for additional sources of funds, supporting the fulfillment of infrastructure, as well as being a facilitator and mediator to various external parties, so that the fulfillment of madrasa needs can be realized. The role of the committee can help the principal so that the quality of education can be improved.